Understanding Rejection between First-and-Second-Grade Elementary Students through Reasons Expressed by Rejecters - García Bacete, Francisco J.; Carrero Planes, Virginia E.; Marande Perrin, Ghislaine; Musitu Ochoa, Gonzalo (Frontiers in Psychology, 2017)
Objective: The aim of this research was to obtain the views of young children regarding their reasons for rejecting a peer. Method: To achieve this goal, we conducted a qualitative study in the context of theory building research using an analysis methodology based on Grounded Theory. The collected information was extracted through semi-structured individual interviews from a sample of 853 children aged six from 13 urban public schools in Spain. Results: The children provided 3,009 rejection nominations and 2,934 reasons for disliking the rejected peers. Seven reason categories emerged from the analysis. Four categories refer to behaviors of the rejected children that have a cost for individual peers or peer group such as: direct aggression, disturbance of wellbeing, problematic social and school behaviors and dominance behaviors. A further two categories refer to the identities arising from the preferences and choices of rejected and rejecter children and their peers: personal identity expressed through preferences and disliking, and social identity expressed through outgroup prejudices. The “no-behavior or no-choice” reasons were covered by one category, unfamiliarity. In addition, three context categories were found indicating the participants (interpersonal–group), the impact (low–high) and the subjectivity (subjective–objective) of the reason. Conclusion: This study provides researchers and practitioners with a comprehensive taxonomy of reasons for rejection that contributes to enrich the theoretical knowledge and improve interventions for preventing and reducing peer rejection.